Platelet reactivity and clinical outcomes following percutaneous coronary intervention in complex higher-risk patients. Issue 2 (February 2022) - Viscusi, Michele M.; Mangiacapra, Fabio; Bressi, Edoardo; Sticchi, Alessandro; Colaiori, Iginio; Capuano, Marialessia; Ricottini, Elisabetta; Cavallari, Ilaria; Spoto, Silvia; Di Sciascio, Germano; Ussia, Gian Paolo; Grigioni, Francesco
Abstract : Aims: To investigate the levels of platelet reactivity and the impact of high platelet reactivity (HPR) on long-term clinical outcomes of complex higher-risk and indicated patients (CHIP) with stable coronary artery disease (CAD) treated with elective percutaneous coronary intervention (PCI). Methods: We enrolled 500 patients undergoing elective PCI for stable CAD and treated with aspirin and clopidogrel. Patients were divided into four groups based on the presence of CHIP features and HPR. Primary endpoint was the occurrence of major adverse clinical events (MACE) at 5 years. Results: The prevalence of HPR was significantly greater in the CHIP population rather than non-CHIP patients (39.9% vs 29.8%, P  = 0.021). Patients with both CHIP features and HPR showed the highest estimates of MACE (22.1%, log-rank P  = 0.047). At Cox proportional hazard analysis, the combination of CHIP features and HPR was an independent predictor of MACE (hazard ratio 2.57, 95% confidence interval 1.30–5.05, P  = 0.006). Conclusion: Among patients with stable CAD undergoing elective PCI and treated with aspirin and clopidogrel, the combination of CHIP features and HPR identifies a cohort of patients with the highest risk of MACE at 5 years, who might benefit from more potent antiplatelet strategies.